Analisis Evapotranspirasi Daerah Irigasi Rawa Sungai Rengas Kecamatan Gandus Kota Palembang - Aryani, Indri Huseli; Nurmeyliandari, Revianty; Baniva, Ratih (Jurnal Teknik Sipil, 2026)
In irrigation system operations, it is important to consider water requirements by conducting an evapotranspiration analysis. This research aims to analyze the level of evapotranspiration in the Rengas River swamp irrigation area, Gandus District, Palembang City, and to compare the evapotranspiration results using four empirical methods. For this purpose, climatological data such as temperature, wind speed, relative humidity, and sunshine duration were collected. The analysis was carried out using various methods to estimate evapotranspiration values from 2019 to 2023: Blaney-Criddle method: considers temperature; Radiation method: considers temperature and solar radiation; Penman method: considers temperature, humidity, wind speed, and solar radiation; and Cropwat Software Version 8.0: considers temperature, humidity, wind speed, and solar radiation. Air temperature plays a key role in determining the level of potential evapotranspiration each year. Among the four empirical methods used, the Blaney-Criddle method produced an average of 4.954 mm/day, the Radiation method 4.697 mm/day, and the Penman method 4.817 mm/day. Cropwat provided a lower estimate, with an average of 3.851 mm/day, while the average actual evapotranspiration value was 3.850 mm/day. Based on the comparison, the Cropwat method is considered the most suitable because it closely matches the actual evapotranspiration value, takes all climatic factors into account, and is recommended by the Food and Agriculture Organization (FAO) in Irrigation and Drainage Paper No. 56 (2006).